Adaptations : from short story to big screen : 35 great stories that have inspired great films / edited by Stephanie Harrison. - Harrison, Stephanie, 1961- (Three Rivers Press, 2005)
Adaptations offers insight into the process of turning a short story into a screenplay, one that, when successful, doesn't take drastic liberties with the text upon which it is based, but doesn't mirror its source material too closely either.